Academic administration affecting student achievement of vocational colleges in Jiangxi province - Yao, Yao; Siththada, Thada (Edelweiss Applied Science and Technology, 2024)
This study examines the impact of academic administration on student achievement in vocational colleges in Jiangxi Province, China. Using a mixed-methods approach, the study synthesized quantitative data from 468 survey respondents and qualitative insights from semi-structured interviews to assess the key factors influencing student achievement. The findings highlighted the impact of the instructional management sector (including Human resources for schools, School teaching resources, School financial resources, Socio-economic status of schools, Management styles of school leaders, teaching program management and school climate) in influencing student achievement (as measured by Professional achievements, Student GPA, Employment satisfaction, Scholarship amount and Competition Awards). The study also identified challenges such as inefficient resource allocation and variable leadership styles. Based on the findings of the study, strategic recommendations were made to enhance academic administration practices aimed at improving the overall quality of student achievement in vocational colleges in Jiangxi Province. The study provides valuable insights into the educational management discourse and offers actionable guidance for policy formulation and institutional development.